DETERMINANTS OF MENTAL HEALTH PSYCHOEDUCATION IMPLEMENTATION AMONG PRIMARY HEALTHCARE WORKERS IN REMBANG REGENCY, INDONESIA: CROSS-SECTIONAL STUDY - Taufiq Akbar; Bagoes Widjanarko; Ayun Sriatmi (Pena Cendekia Insani, 2026)
Mental health remains a growing public health challenge, while psychoeducation services at the primary care level are not yet optimally implemented. This study analyzed factors associated with the implementation of mental health psychoeducation services among healthcare workers in Public Health Centers in Rembang Regency, Indonesia, using a multilevel analytical approach. A cross-sectional study was conducted among 233 healthcare workers selected from 359 eligible participants using stratified random and total sampling. Data were collected using validated questionnaires and analyzed using chi-square tests, logistic regression, and multilevel mixed-effects analysis. The results showed that 60.1% of psychoeducation services were not achieved. In the final multilevel model, profession (OR = 4.464; 95% CI : 1.882–10.584), knowledge (OR = 3.367; 95% CI : 1.465–7.738), and attitude (OR = 3.368; 95% CI : 1.458–7.782) were significantly associated with service implementation, while leadership was significant at the organizational level (OR = 4.418; 95% CI : 1.754–11.126). The model showed meaningful clustering across Public Health Centers (ICC = 22.28%). In conclusion, the implementation of mental health psychoeducation services is influenced by both individual and organizational factors, with leadership representing the most important organizational determinant. Strengthening leadership and improving workforce capacity may enhance these services in primary healthcare.